BUKU CETAK DAN DIGITAL: PREFERENSI MEMBACA BACAAN NONFIKSI DI KALANGAN PENELITI DAN AKADEMISI - Puspita Dewi, Sarwendah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2022)
Reading habit in today’s society comes to a new dimension. Digital or electronic books (e-books) have been considered in the groups of reading sources in the present era. It means that printed books are no longer dominant as the only reading source. Since this is new and inevitable, society seems to have no choice but to follow the development. Therefore, this study was conducted to gain specific information/study about the preferences of the public, especially researchers and academics, in reading nonfiction books through printed and digital books. This research used quantitative methods from the survey result and descriptive analysis techniques to explain the data. The result showed that among 105 respondents consisting of researchers and academics, they prefer to read academic materials in printed format rather than digital ones. Emotional impression, eye comfort, level of understanding, ease, lack of technological engagement, and employment are crucial, making most respondents prefer to read books in print rather than digital (electronic). Thus, this study shows that the availability of digital books does not necessarily shift the existence of printed books because when the respondents are asked to choose, they, researchers and academics, actually prefer choosing nonfiction books in printed form over digital ones.